Energetic performance analysis of a ground-source heat pump system with latent heat storage for a greenhouse heating - Benli, Huseyin (Pergamon-Elsevier Science Ltd, 2011)
In this study, a ground-source heat pump heating system with a latent heat thermal storage tank was designed while its thermal energy storage performance was investigated. The heating system mainly consists of a ground heat exchanger, a heat pump, a cylindrical latent heat thermal storage tank, measuring units and a heating space of model-sized glass greenhouses with 30 m(2), located in the greenhouse district of Firat University, Elazig, in Turkey. In the experiments, the performance characteristics of a ground-source heat pump greenhouse heating system with a 246 m horizontal 12.7 mm nominal diameter horizontal closed-loop ground heat exchanger and the use of phase change materials (PCM) for energy saving and management in greenhouses were investigated. The heating coefficient of performances of the ground-source heat pump (COP(HP)) and the overall system (COP(sys)) are obtained, to be in the range of 2.3-3.8 and 2-3.5 respectively. Although significant savings are possible with this heating system, a substantial investment in equipment and facilities may be required. The experiments results were obtained from October to May in heating seasons of 2005-2006. The results showed that the utilization of ground-source heat pump-PCM is suitable for greenhouse heating in this district. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Ground-source heat pump (GSHP); Phase change material (PCM); Renewable energy